2009
DOI: 10.1002/jmr.952
|View full text |Cite
|
Sign up to set email alerts
|

DNA, oligosaccharides, and mononucleotides stimulate oligomerization of human lactoferrin

Abstract: Using small-angle X-ray scattering (SAXS), light scattering (LS), and soft laser ablation we have shown that lactoferrin (LF) in solution at neutral pH is oligomerized in the absence of salt or at physiological salt concentrations. The level of oligomerization depends on the concentration of LF, KCl or NaCl, and on the duration of the protein storage in solution. At the concentrations comparable with those in human milk (1-6 mg/ml), the average radius of gyration (R(g)) values of LF can attain 400-480 A, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 28 publications
(64 reference statements)
1
31
1
Order By: Relevance
“…In order to identify the homogeneity of HMW-bLf, analysis of the components of HMW-bLf was further carried out by dissociating the complex into its dimeric and monomeric forms in the presence of 1 M NaCl as described earlier for hLf [11]. The study reported that hLf oligomers dissociate fast and almost completely to monomers in the presence of high concentrations (≥1.0 M) of Na + or K + .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to identify the homogeneity of HMW-bLf, analysis of the components of HMW-bLf was further carried out by dissociating the complex into its dimeric and monomeric forms in the presence of 1 M NaCl as described earlier for hLf [11]. The study reported that hLf oligomers dissociate fast and almost completely to monomers in the presence of high concentrations (≥1.0 M) of Na + or K + .…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, 3 mg mL −1 of HMW-bLf was dissolved in 50 mM Tris HCl (pH 7.5) containing 1 M NaCl and incubated for 1 day at 37°C. SDS-PAGE was carried out to analyze the dissociation of HMW-bLf complex into its components [11]. Western blotting was carried out to analyze the obtained protein bands by goat anti- bLf (Bethyl Laboratories) diluted in the ratio of 1∶1000 to confirm the presence of lactoferrin.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies concluded that iron binding activity and restricting iron metabolism are the foundation of inhibiting the growth of microbe (Caraher et al 2007;Zarember et al 2007). Besides, some reports demonstrated that the ability to bind to other macromolecules (proteins, DNA) (Baker and Baker 2009;Nevinskii et al 2009) may also play important role in the many functions. The modeled distribution of surface charge (Fig.…”
Section: Discussionmentioning
confidence: 99%